WAYS OF DEVELOPMENT AND FORMATION OF ISLAMIC BANKING IN MODERN ECONOMY - Furkatovna, Inoyatova Kamola; Esanovna, Egamova Makhfurat; Rashidovna, Majidova Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the origin and development of Islamic banks. The differences between the traditional and Islamic banks are compiled.